2006
DOI: 10.2355/isijinternational.46.420
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of the CaO–Al2O3–SiO2 System

Abstract: Thermal conductivity of the CaO-Al 2 O 3 -SiO 2 system, which is one of the most important silicate melts in iron-and steelmaking processes, was measured using non-stationary hot wire method in the range from liquidus temperature to 1 873 K. Measurements were carried out at various compositions, and iso-thermal conductivity line of the CaO-Al 2 O 3 -SiO 2 system was drawn in iso-thermal sections at 1 673 K, 1 773 K, and 1 873 K. Thermal conductivity decreased with basicity increase, when CaO/SiO 2 ratio is sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 9 publications
3
83
0
Order By: Relevance
“…44) In the case of viscosity, the temperature dependency is simply described by the Arrhenius equation; from which the apparent activation energy can be derived. As an analogy to viscosity, Kang and Morita 23) expressed thermal conductivity as an Arrhenius-type equation, based on the relationship between the mean free path and the number of thermally broken bonds. Using this equation, values for the apparent activation energy of thermal conductivity were obtained, and are plotted in Fig.…”
Section: Relations Between Activation Energy and Its Molten Structurementioning
confidence: 99%
“…44) In the case of viscosity, the temperature dependency is simply described by the Arrhenius equation; from which the apparent activation energy can be derived. As an analogy to viscosity, Kang and Morita 23) expressed thermal conductivity as an Arrhenius-type equation, based on the relationship between the mean free path and the number of thermally broken bonds. Using this equation, values for the apparent activation energy of thermal conductivity were obtained, and are plotted in Fig.…”
Section: Relations Between Activation Energy and Its Molten Structurementioning
confidence: 99%
“…[2][3][4] The structural unit of aluminate anion is very complicated and thus Al coordination number varies from 4 to 6, viz. AlO 4 , AlO 5 and AlO 6 units.…”
Section: Introductionmentioning
confidence: 99%
“…54) However, it has also been reported that the thermal conductivity of a molten CaOAl2O3-SiO2 slag exhibits a negative deviation from the expected linearity against 1/T. 7) This disagreement may imply that the theory of heat conduction in crystalline solid as expressed by Eq. (4) is not valid in the molten silicate.…”
Section: Temperature Dependence Of Thermal Conductivitymentioning
confidence: 74%
“…6,[26][27][28] Initially, the Na2O-SiO2 slag system was selected for thermal conductivity measurements, taking advantage of its relatively low melting point. 2,6,26,27,[30][31][32] Soon after, the hot wire method was also established for measuring the thermal conductivity of the CaO-Al2O3-SiO2, 7,[26][27][28] CaO-Al2O3-SiO2-MgO, 31) and CaO-SiO2-FeOx slag systems. 32,33) The fundamental measurement principle of the hot wire method can be described as follows: First, a thin thermoresistor wire is placed vertically in the middle of a molten sample.…”
Section: Non-steady-state Methodsmentioning
confidence: 99%
See 1 more Smart Citation